Studies (with n application) related to group technology (GT) - 199452 Zulfikar Ali Abdul Aziz (Sekudai, Johor : UTM, 1986)
Thesis (Bachelor in Mechanical Engineering) - Universiti Teknologi Malaysia, 1986